N-acetylglucosamine-Mediated Expression of nagA and nagB in Streptococcus pneumoniae - Afzal, Muhammad; Shafeeq, Sulman; Manzoor, Irfan; Henriques-Normark, Birgitta; Kuipers, Oscar P. (Frontiers in Cellular and Infection Microbiology, 2016)
In this study, we have explored the transcriptomic response of Streptococcus pneumoniae D39 to N-acetylglucosamine (NAG). Transcriptome comparison of S. pneumoniae D39 wild-type grown in chemically defined medium (CDM) in the presence of 0.5% NAG to that grown in the presence of 0.5% glucose revealed elevated expression of many genes/ operons, including nagA, nagB, manLMN, and nanP. We have further confirmed the NAG-dependent expression of nagA, nagB, manLMN, and nanP by β-galactosidase assays. nagA, nagB and glmS are putatively regulated by a transcriptional regulator NagR. We predicted the operator site of NagR (dre site) in PnagA, PnagB and PglmS, which was further confirmed by mutating the predicted dre site in the respective promoters (nagA, nagB and glmS). Growth comparison of ΔnagA, ΔnagB and ΔglmS with the D39 wild-type demonstrates that nagA and nagB are essential for S. pneumoniae D39 to grow in the presence of NAG as a sole carbon source. Furthermore, deletion of ccpA shows that CcpA has no effect on the expression of nagA, nagB and glmS in the presence of NAG in S. pneumoniae.